Light Regulation of Chlorophyll and Glycoalkaloid Biosynthesis During Tuber Greening of Potato S. tuberosum - Okamoto, Haruko; Ducreux, Laurence J. M.; Allwood, J. William; Hedley, Pete E.; Wright, Alison; Gururajan, Vidyanath; Terry, Matthew J.; Taylor, Mark A. (Frontiers in Plant Science, 2020)
Potato, S. tuberosum, is one of the most important global crops, but has high levels of waste due to tuber greening under light, which is associated with the accumulation of neurotoxic glycoalkaloids. However, unlike the situation in de-etiolating seedlings, the mechanisms underlying tuber greening are not well understood. Here, we have investigated the effect of monochromatic blue, red, and far-red light on the regulation of chlorophyll and glycoalkaloid accumulation in potato tubers. Blue and red wavelengths were effective for induction and accumulation of chlorophyll, carotenoids and the two major potato glycoalkaloids, -solanine and -chaconine, whereas none of these accumulated in darkness or under far-red light. Key genes in chlorophyll biosynthesis (HEMA1a, encoding the rate-limiting enzyme glutamyl-tRNA reductase, GSA, CHLH and GUN4) and six genes (HMG1, SQS, CAS1, SSR2, SGT1 and SGT2) required for glycoalkaloid synthesis were also induced under white, blue, and red light but not in darkness or under far-red light. These data suggest a role for both cryptochrome and phytochrome photoreceptors in chlorophyll and glycoalkaloid accumulation. The contribution of phytochrome was further supported by the observation that far-red light could inhibit white light-induced chlorophyll and glycoalkaloid accumulation and associated gene expression. Transcriptomic analysis of tubers exposed to white, blue, and red light showed that light induction of photosynthesis and tetrapyrrole-related genes grouped into three distinct groups with one group showing a generally progressive induction by light at both 6 h and 24 h, a second group showing induction at 6 h in all light treatments, but induction only by red and white light at 24 h and a third showing just a very moderate light induction at 6h which was reduced to the dark control level at 24 h. All glycoalkaloid synthesis genes showed a group one profile consistent with what was seen for the most light regulated chlorophyll synthesis genes. Our data provide a molecular framework for developing new approaches to reducing waste due to potato greening.